BALANCING LOCAL BUDGETS UNDER THE CONDITIONS OF FINANCIAL DECENTRALIZATION - V.V., Mamonova; O.O., Vasyleha (Pressing Problems of Public Administration, 2016)
Grounded theoretical and methodological approaches and formed recommendations for balancing the localbudgets during the  nancial decentralization. Among them – the introduction of the compensator of thecorporate income tax in the form of interbudgetary transfer; amend the legislation governing to gathering ofexcise tax; execute expenditures on training of workers in vocational schools  nanced from the state budget;streamline the compensation mechanism for preferential thoroughfare some categories of citizens.